AN EMPIRICAL ANALYSIS ON CHALLENGES AND PERFORMANCE OF YOUNG ENTREPRENEURS IN TENKASI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Entrepreneurs are the ones who work hard, take risks, learn from their failure and succeed with profit and recognition. Young entrepreneurs of India foster the nation’s economy with their brilliance and firmness. The present study aims to identify the challenges and performance of young entrepreneurs in Tenkasi District. Descriptive research design is used and quantitative empirical research approach is employed. The samples of 150 young entrepreneurs in Tenkasi district are identified with the help of the concerned District Industrial Centre.